2022
DOI: 10.3389/fsurg.2022.1001350
|View full text |Cite
|
Sign up to set email alerts
|

Case report: Castleman’s disease involving the renal sinus resembling renal cell carcinoma

Abstract: IntroductionCastleman's disease (CD) is a rare benign lymphoproliferative disease that frequently involves the mediastinal thorax and the neck lymph nodes. It rarely affects extrathoracic presentations, with even fewer presentations in the renal sinus.Patient concernsIn this report, we present a case of a 40-year-old woman with no significant past medical history who presented Castleman's disease arising in the renal sinus.Diagnosis and interventionsThe patient visited our hospital with the chief complaint of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…This case report adds to the existing literature on the variable manifestations of Castleman disease and emphasizes the value of imaging and histopathological analysis in arriving at an accurate diagnosis. Since it is rare, few previously published studies reported cases of CD involving the renal sinus (Table 1) (8)(9)(10)(11)(12)(13)(14)(15). The presentation of the patients is unspecific in all of the reported cases.…”
Section: Discussionmentioning
confidence: 99%
“…This case report adds to the existing literature on the variable manifestations of Castleman disease and emphasizes the value of imaging and histopathological analysis in arriving at an accurate diagnosis. Since it is rare, few previously published studies reported cases of CD involving the renal sinus (Table 1) (8)(9)(10)(11)(12)(13)(14)(15). The presentation of the patients is unspecific in all of the reported cases.…”
Section: Discussionmentioning
confidence: 99%